Character Values In The Thematic Learning Of Elementary School - Ari Setiawan; Syarief Fajaruddin; Makmur Haji Harun; Yohana Sumiyati; C. Indah Nartani; Fitriana Fitriana (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2020)
The study aims at identifying the character values that appear in the thematic learning of elementary school. The approach that has been adopted in conducting the research is the quantitative approach. The subjects who had been selected using random cluster sampling were 180 students from the elementary schools located in the Province of Yogyakarta Special Region. The study results show that the instrument that has been administered to identify the character values has a high value of content validity. The components that have been established are namely honest, disciplined, responsible, polite, caring, and self-confident.